Animal models of developmental dyslexia: Where we are and what we are missing. (December 2021) - Lampis, Valentina; Ventura, Rossella; Di Segni, Matteo; Marino, Cecilia; D'Amato, Francesca Romana; Mascheretti, Sara
Highlights: Animal models of neurodevelopmental disorders are useful. Animal models of some DD-candidate genes have been tested. Imaging investigation is lacking in DD animal models. Environmental manipulation has never been implemented in DD animal models. Investigation of DD risk factors in different developmental windows is absent. Abstract: Developmental dyslexia (DD) is a complex neurodevelopmental disorder and the most common learning disability among both school-aged children and across languages. Recently, sensory and cognitive mechanisms have been reported to be potential endophenotypes (EPs) for DD, and nine DD-candidate genes have been identified. Animal models have been used to investigate the etiopathological pathways that underlie the development of complex traits, as they enable the effects of genetic and/or environmental manipulations to be evaluated. Animal research designs have also been linked to cutting-edge clinical research questions by capitalizing on the use of EPs. For the present scoping review, we reviewed previous studies of murine models investigating the effects of DD-candidate genes. Moreover, we highlighted the use of animal models as an innovative way to unravel new insights behind the pathophysiology of reading (dis)ability and to assess cutting-edge preclinical models.